2013
DOI: 10.4236/ajps.2013.45141
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organic Manures on Yield and Quality of Rice (<i>Oryza sativa</i> L.) and Blackgram (<i>Vigna mungo</i> L.) in Rice-Blackgram Cropping Sequence

Abstract: Field experiments were conducted at Tamil Nadu Agricultural University, Coimbatore during rabi and summer seasons of 2007-2008 and 2008-2009 to study the influence of organic manures (enriched farmyard manure compost, vermicompost, farmyard manure + neem cake, enriched farmyard manure compost + vermicompost + farmyard manure, composted poultry manure and enriched poultry manure compost) and recommended NPK fertilizers on yield and quality of rice and blackgram in rice-blackgram cropping sequence. Based on fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 1 publication
5
14
0
Order By: Relevance
“…The number of seeds per pod was significantly higher with 75% RDNF+25% N through vermicompost (11.68) in the pooled data. These results are in conformity with those of Singh and Gujar (2012) and Sangeetha et al (2013).…”
Section: No Of Pods Plant -1supporting
confidence: 93%
“…The number of seeds per pod was significantly higher with 75% RDNF+25% N through vermicompost (11.68) in the pooled data. These results are in conformity with those of Singh and Gujar (2012) and Sangeetha et al (2013).…”
Section: No Of Pods Plant -1supporting
confidence: 93%
“…The combined treatment effect on other yield parameters simultaneously might have contributed to maximum haulm yield. Similarly, the haulm yields of blackgram were markedly increased due to the application of organic manure [ 29 ]. An increase of 59% in Typic Haplustalf and 60% in Typic Rhodustalf of haulm yield was recorded by CRH + 50% RDF + Rhizobium + phosphobacterium (T 10 ) over control.…”
Section: Resultsmentioning
confidence: 99%
“…The integrated nutrient management technique resulted in a positive influx of nutrients by increasing organic carbon content, available nitrogen, phosphorus, and potassium. It was found that the application of enriched poultry manure compost on equal N basis (2.3 t·ha , which was however comparable with composted poultry manure (Sangeetha et al, 2013).…”
Section: Yield Of Ricementioning
confidence: 89%